Diversity of Macrophages in Lung Homeostasis and Diseases - Hou, Fei; Xiao, Kun; Tang, Li; Xie, Lixin (Frontiers in Immunology, 2021)
Lung macrophages play important roles in maintenance of homeostasis, pathogen clearance and immune regulation. The different origins of pulmonary macrophages and their roles in lung diseases have attracted attention in recent years. Tissue-resident alveolar macrophages (TR-AMs), monocyte-derived alveolar macrophages (Mo-AMs) and interstitial macrophages (IMs) are the major macrophage populations in the lung and have unique characteristics in both steady-state conditions and disease states. The different characteristics of these three types of macrophages determine the different roles they play in the development of disease. Therefore, it is important to fully understand the similarities and differences between these three types of macrophages for the study of lung diseases. In this review, we will discuss the physiological characteristics and unique functions of these three types of macrophages in acute and chronic lung diseases. We will also discuss the potential interactions between lung macrophages and possible ways to target macrophages in lung diseases.